Prolonged Recovery From General Anesthesia Possibly Related to Persistent Hypoxemia in a Draft Horse - Dupont, Julien; Serteyn, Didier; Sandersen, Charlotte (Frontiers in Veterinary Science, 2018)
Horses are susceptible to developing large areas of pulmonary atelectasis during recumbency and anaesthesia. The subsequent pulmonary shunt is responsible for significant impairment of oxygenation. Since ventilation perfusion mismatch persists into the post-operative period, hypoxemia remains an important concern in the recovery stall. This case report describes the diagnosis and supportive therapy of persistent hypoxemia in a 914 kg draft horse after isoflurane anaesthesia. It highlights how challenging it can be to deal with hypoxemia after disconnection from the anaesthesia machine and how life-threatening it can become if refractory to treatment. Furthermore, it stresses the point on the interactions between hypoxemia and other factors, such as residual drug effects and hypothermia, that should also be considered in the case of delayed recovery from general anaesthesia.